Detective reasoning in criminal investigation: Integrating abduction, retroduction, deduction, and induction into the national decision model (NDM) - Jang, Minhwan (International journal of police science & management, 2025)
This article critiques the current national decision model (NDM) used primarily by police organizations in England and Wales, highlighting its limitations in supporting detective decision-making processes. Although the NDM is effective for ensuring accountability and ethical considerations, it lacks an explicit reasoning stage crucial for the complex decision-making required in detective work. By examining the cognitive processes of abduction, retroduction, deduction and induction, the article argues for the integration of reasoning into the NDM to enhance its utility in investigative contexts. This proposed revision aims to improve decision-making outcomes, reduce the risk of miscarriages of justice and better support detectives in their critical decision-making. The article suggests that a more structured and systematic approach to reasoning within the NDM could lead to more transparent and effective decision-making practices, ultimately benefiting both police practitioners and the communities they serve.